Studies at the Faculty of Economics of Vilnius University: Present State and Prospectives - Galinienė, Birutė; Martinavičius, Jonas; Čekanavičius, Linas; Miškinis, Algirdas (Ekonomika, 2003)
The paper is devoted tot to review of the current situation with the study programs offered by the Faculty of Economics, of Vilnius University: their status quo. their strengths and weaknesses. and their prospective in the future. The “diagnostic” part presented here is to the large extent based on the results of analysis that was recently carried out at the Faculty of Economic. while preparing its study programs for an international assessment and accreditation, whereas speculations about the future prospective of the Faculty is based on its Development Plan. The findings of the analysis reveal that the strong points of the study programs offered by the Faculty of Economics are the following ones: long-standing and reputable traditions of economic studies (the beginning of which can be traced back to the year IB03. when the Department of Political Economy - first of the kind in the world - was established at Vilnius University), experienced academic staff, attractive study programs, an accumulated experience of participation in the international study, research and academic exchange projects. However, the following features can be counted as weaknesses and potential threats to the sustainability of the level achieved: “brain drain” and an ageing of staff, insufficient research efforts. as well as lack of serious incentives for it, rather slow introduction of modem teaching methods to the study process, insufficient development of practical skills (parallel to the theoretical knowledge) of students. The paper ends with the elaborate description and substantiation of plans for the development of the Faculty’s intellectual and pedagogical potential, and study infrastructures, in order to ensure sustainability and enhancement of the academic standards at the Faculty of Economics.